Determination of Amylase Rich Malted Mixes (ARMMS) for Improvement of Nutritional and Health Status of Pre School Children - Khader , Vijaya; Maheswari , K. Uma (Research Highlights in Disease and Health Research Vol. 8, 2023)
The present study aims to evaluate Amylase Rich Malted Mixes (ARMMS) to Improve the Nutritional and Health Status of Pre School Children. Flours of germinated cereals that are rich in the enzyme amylase constitute amylase- rich foods (ARF). Even small quantities of this type of foods liquefy and reduce the bulk of the cereal- based diet. Material required for the study such as ragi, wheat, green gram, sugar and milk powder were procured from local market in Hyderabad, India. The formulated ARMM and products were subjected to five point hedonic scales for organoleptic evaluation. The results indicated that the energy and protein densities of the blends were high and ranged from 0.7 to 0.8 kcal and 0.7 to 1.1g/100kcal, respectively. The densities of vitamin A, calcium and iron were low, while those of folate and iodine were high. All the porridges had over 600cP viscosity before the addition of ARF. The results of physical parameters reveal that malting decreased grain length, width, kernel weight (0.45 to 19.0 g), volume (0.50 –31.2 ml), hardness (1.12 to 5.9 kg/cm2) and reduced the bulk density. Wheat malted mix had significantly higher (P<0.05) fat (2.27g), carbohydrate (98.0 g) and calorie (396 kcal) content. Significantly higher (P<0.05) calcium (440 mg), thiamine (0.7 mg) and riboflavin (0.9 mg) content were observed in ragi malted mix compared to native and germinated grains. When compared to the native grains and malted mixes germinated green gram had significantly higher protein (33.0 g), fibre (11.5 g), iron (8.0 g) and vitamin C (157.8 mg) content. The incorporation of malted green gram mix and skimmed milk powder to the wheat malted mix and ragi malted mix help to improve nutritive value of the malted mixes, especially protein, energy, iron, calcium and ‘B’ complex vitamins. Based on the nutritive value the Amylase Rich Malted Mixes (ARMMS) to Improve the Nutritional and Health Status of Pre School-Children.